THE USE OF GRIGNARD REAGENT IN PHEROMONE SYNTHESIS FOR PALM WEEVIL (Rhynchorus, Sp) - Warsito Warsito; Edi Priyo Utomo; Achmad Ashadi; Satriyo Santosa (Indonesian Journal of Chemistry, 2003)
In an integrated controlling system of palm weevil, using of synthetic feromoid is strickly needed. The research is aimed to synthesize pheromone which secreted by the weevil, e.g. 4-methyl-5-nonanol (R. ferrugineus) and 3-methyl-4-octanol (R. schach) through Grignard reagent which formed in situ.The synthesis was proceded by retrosynthesis to determine the precursor, valeraldehyde. The precursor was reacted with Grignard reagent of sec-amyl magnesium bromide (R. ferrugenieus) and sec-butyl magnesium bromide (R. shach) which made in situ. Characterization of the synthetic molecular pheromone was performed by Gas Chromatography-mass spectroscopy and Fourier Transformed Infra Red. The bioassay of the molecule was carried out by olfactometer.The result showed that the conversion of the reactions were 51.28% (4-methyl-5-nonanol) and 85.90% (3-methyl-4-octanol). The character of physico-chemical and bioactivity of the synthetic pheromone are identic with natural pheromones.